PANDANGAN TOKOH MASYARAJAT TENTANG KAFA’AH SEBAGAI DASAR MEMBANGUNG KELUARGA SAKINAH DI DESA PATOKPICIS KECAMATAN WAJAK KABUPATEN MALANG - Muhammad Amrul Afifi; Khoirul Asfiyak; Shofiatul Jannah (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Every human being certainly cannot live alone without other humans, therefore humans were created in pairs. God arranges it in marriage. Marriage is an inner and outer marriage between a man and a woman as husband and wife with the aim of forming a lasting and eternal family based on the One Godhead. Generally people will want an eternal marriage and (sakinah), because this is the main goal of a marriage, a sakinah family will foster peace in the heart, a sakinah family can be achieved by determining kafa'ah before marriage, kafa'ah is between candidates for marriage. husband and wife, the event covered several things including wealth, social level, religion, and descent. By determining kafa'ah before marriage, it is hoped that it will facilitate the achievement of the ideals of the sakinah family which is a dream for every human being and can minimize the existence of long squabbles and can prevent divorce.Kata kunci: Views of comunity leaders, kafa’ah, sakinah family